2007
DOI: 10.1002/cpp.527
|View full text |Cite
|
Sign up to set email alerts
|

Researching clients' experiences: A review of qualitative studies

Abstract: This article aims to explore the role that clients play in research and how their experiences can contribute to psychotherapy process research. Following a broad outline of the findings of earlier process research, arguments why clients have not been at the forefront of researchers' methodologies are offered against those who recognize the value and importance of asking clients directly about their experiences. Examples of a range of studies are discussed where clients' views and experiences of different thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 38 publications
(47 reference statements)
1
55
0
6
Order By: Relevance
“…The preceding phases in preparation for this study were: i) qualitative interviews conducted with bipolar individuals concerning their experiences of anxiety and their views about psychological treatment; and ii) a series of focus groups conducted with services users and health professionals to develop and refine the treatment manual employed here. The findings of both previous phases have informed the content and presentation of the therapy evaluated here, consistent with wider recogntion of the crucial importance of involving service users in treatment development, planning and provision [14]. There is an increasing recognition that qualitative methods are better suited to understanding the perspectives of service users and capitalizing on their insights [15].…”
Section: Introductionsupporting
confidence: 61%
“…The preceding phases in preparation for this study were: i) qualitative interviews conducted with bipolar individuals concerning their experiences of anxiety and their views about psychological treatment; and ii) a series of focus groups conducted with services users and health professionals to develop and refine the treatment manual employed here. The findings of both previous phases have informed the content and presentation of the therapy evaluated here, consistent with wider recogntion of the crucial importance of involving service users in treatment development, planning and provision [14]. There is an increasing recognition that qualitative methods are better suited to understanding the perspectives of service users and capitalizing on their insights [15].…”
Section: Introductionsupporting
confidence: 61%
“…Lambert () asserted that to reduce negative effects of therapy, we must first be capable of predicting them. Therapists have limited abilities in predicting deterioration in clients (Hannan et al., ), and research has consistently found discrepancies between client and practitioner perceptions (Hodgetts & Wright, ; Llewellyn, ), particularly when client views of therapy are negative (Von Below & Werbart, ). Researchers have attempted to identify factors associated with non‐response.…”
Section: Introductionmentioning
confidence: 99%
“…Metcalf & Thomas 1994, Couture & Sutherland 2004, Crowe & Luty 2005). There is emerging advocacy in psychotherapy research for the use of qualitative‐oriented process methods (McLeod 2001, Elliot 2002, Hodgetts & Wright 2007). Ozkan (2004) has also suggested that there is a general lack of writing in qualitative research that sheds light on the ‘nuts and bolts’ of the qualitative data analysis.…”
Section: Introductionmentioning
confidence: 99%